Rushing to the end: Participants perceptions of demotivating aspects of online surveys - Martins,João (2020)
More and more social science studies are now acquiring data through the internet, reaching participants online. Some participants start out engaged and motivated to participate, but progressively slide into «rushing behaviors». We inquired experts in survey responding about when, in online studies, they would feel a desire for rushing (defined as speeding with no concerns about the quality of responses). This qualitative approach uncovered Repetition, Survey length and No interest in topic as the three main features that would motivate these participants to rush in surveys. Subsequent inquiry of the same participants indicated that repetition concerns the type of questions made (more than stimuli or task), the execution of the same task more than 5-6 times, or for more than 6 minutes. Survey length concerns a preference for shorter surveys, as well as the subjective experience in which length exceeds previously set expectations (i.e., longer than announced), contributing to rushing by effectively lowering the hourly pay rate as the survey increases in length. Interest in topic was reported to be consistently low, despite not being the main reason to quit the survey. However, a change in expected level of interest in the middle of the survey is reported as a factor that will promote rushing behaviors. We discuss these data as informative regarding how pre-tests of surveys can benefit from these participants expertise.